Exploring the Impact of Super Blue Moons on Science and Spirituality - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2024)
This research examines the complex meaning of super blue moons, tying together spiritual and cultural interpretations with scientific explanations from different backgrounds. According to science, super blue moons are uncommon astronomical occurrences that combine the features of a blue moon and a supermoon, each adding to the moon's increased apparent prominence. The lunar phenomenon holds great cultural and spiritual significance throughout several traditions. Religious texts like the Holy Quran and the Bhagavad Gita and Indigenous beliefs, make this clear. The moon is frequently linked to divine appearances and spiritual ceremonies. Scholars such as Al-Ghazali and Vine Deloria Jr. describe how current philosophy perceives the convergence of science and spirituality in comprehending moon phenomena. This study offers an in-depth analysis of the resonance of super blue moons with various worldviews. It also emphasizes how they might serve as a hub for integrating interpretations from spiritual and cultural traditions with scientific understanding.